Cheetah Acinonyx jubatus ecology in the Kruger National Park : a comparison with other studies across the grassland-woodland gradient in African savannas - Du Toit, J.T. (University of Pretoria, 2013)
Dissertation (MSc (Zoology))--University of Pretoria, 2006.